A concepção de ciência e a formação docente em ciências naturais - Ody, Leandro Carlos (2015)
This work aims to present the possible impacts thatthe conceptions of science, represented by internalism and externalism, bring to the formationof educators in the field of natural sciences. We also bring forward a position that enables dialogue between these two different visions. For that, we reconstruct the main characteristics of these two epistemological positions based on thinkers who represent each one. Internalism understands science from its internal rationality and externalism understands it considering elements that extrapolate its internal operations, considering philosophical, social and historical issues, important to build a science image. We analyze the National Curriculum Guidelines related to Biology, Physics and Chemistry courses to seek elements of internalism and externalism in each of them. Moreover, it is pointed out possible consequences when only of one of them is considered to form future educators in this areas. Finally, as the central thesis, the fallibility mentality is set as an alternative epistemological stance, because it appears more flexible and open to dialogue and changes of modern complex societies. We believe that this model can guide the formation of those educators contemplating elements of the two relevant previous positions in the process. To reach the aims, inside the qualitative paradigm, the bibliographic and documentary research were the components of the methodology, where internalism features are based on Karl Popper's (1993) and Carl Hempel’s (1981) ideas. On the other hand, externalism was discussed focused on Thomas Kuhn's theories (2000). Furthermore, we bring together the main constituents of the National Curriculum Guidelines for Biology, Physics and Chemistry courses, identifying internalism and externalism elements present in them. In this way, we could propose a synthesis of the two views of science from fallibilism. This work is significant because it points out the clear epistemological foundation need to comprehend what science is. It is also relevant to debate about the consequences of taking only one of these grounds, or a dialogue between them, as a guide of educational activities related to teacher formation in the natural sciences area. We hope to subsidize the formation teacher process in natural sciences in a way it can be integral, dialogic, democratic, open and interdisciplinary, based on a fallibilist mentality.